Technology Adoption In Manufacturing Industry and Its Policy Implication - Rosadi, A. Husni Y. (Journal of S&T Policy and R&D Management, 2014)
Technology adoption is an attempt to accelerate controlling, learning, and utilizing technology from the outside. This will encourage the organization to be able to improve its product, process and competitiveness. A survey conducted by the Ministry of Research and Technology in collaboration with the Agency for the Assessment and Application of Technology on large manufacturing industries (national private, SOE and FI) in Indonesia showed that: (1) respondents conduct technology adoption due to the awareness of the importance of technology innovation in improving companyâs performance; (2) the mechanism of technology adoption is mostly done by purchasing machinery and/or equipment from vendors or suppliers, and only few is done by license; and (3) most of national private companies and FIs adopt technology from other country, while the SOEs tend to utilize domestic technology. Some policy implications are suggested: (1) provide incentives for company utilizing a technology; (2) prepare competent human resource to encourage mechanism of technology adoption on industry; (3) encourage research activity in company and consortium and partnership research activity; and (4) build research area allowing every innovation actor to interact with each other.